2021
DOI: 10.1038/s41598-021-86420-x
|View full text |Cite
|
Sign up to set email alerts
|

Lower local recurrence rate after robot-assisted thoracoscopic esophagectomy than conventional thoracoscopic surgery for esophageal cancer

Abstract: The oncological advantages of robot-assisted thoracoscopic esophagectomy (RATE) over conventional thoracoscopic esophagectomy (TE) for thoracic esophageal cancer have yet to be verified. In this study, we retrospectively analyzed clinical data to compare the incidences of recurrence within the surgical field after RATE and TE as an indicator of local oncological control. Among 121 consecutive patients with thoracic esophageal or esophagogastric junction cancers for which thoracoscopic surgery was indicated, 51… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…A total of 1027 records were identified after automatically and manually removing duplicate records, and 18 full-text studies met the eligibility criteria for inclusion after the final assessment. [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] The selection strategy and procedure are summarized in the PRISMA flow diagram (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 1027 records were identified after automatically and manually removing duplicate records, and 18 full-text studies met the eligibility criteria for inclusion after the final assessment. [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] The selection strategy and procedure are summarized in the PRISMA flow diagram (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 11 studies analyzed postoperative 90-day mortality in each group. 41,[43][44][45][46][47][48][49][50]52,55 The pooled results of the metaanalysis indicated that there was no significant difference in 90-day mortality between the two groups [0.28% (95% CI: 0%-0.68%) vs 0.66% (95% CI: 0.16%-1.16%); OR = 0.87; 95% CI: 0.40-1.92; P = 0.73]. A low heterogeneity was observed from the synthesized results (I² = 0%; P = 0.92) (Fig.…”
Section: -Day Mortalitymentioning
confidence: 99%
See 2 more Smart Citations
“…The treatment center published more than one article with overlapping patients. Motoyama ( 32 ) found that RAMIE could reduce the incidence of recurrence at the surgical site. Long-term outcomes, such as overall survival (OS) and disease-free survival (DFS), must be compared between RAMIE and VAMIE.…”
Section: Discussionmentioning
confidence: 99%